Impacts of COVID-19 Pandemic on Employees’ Anxiety and Safety Behavior at Higher Educational Institutions in Banjarmasin - Rizky Nastiti; Devi Rusvitawati (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2021)
The policy to return to work amidst the pandemic has caused anxiety among employees, including those who work at universities and colleges. In order to maintain organization’s performance in the era of COVID-19, the management needs to pay attention to employees’ adjustment and well-being. Moreover, figuring out employees’ anxiety level and safety behavior during the pandemic will help the managements ease their employees’ anxiety and improve their work performance. Thus, this study focuses on the impacts of COVID-19 on employees’ anxiety and safety behavior at higher educational institutions in Banjarmasin. A total of 78 responses were collected from employees of higher educational institutions in Banjarmasin. From the data analysis, it was found that physical concerns and psychological concerns had significant impacts on anxiety and safety behavior. This study offers suggestions for institutions to provide adequate protective equipment safety and enforce their human resource management to help their employees cope with new work environment.